Is Mean Platelet Volume Really a Severity Marker for Obstructive Sleep Apnea Syndrome without Comorbidities? - Sinem Nedime Sökücü; Cengiz Özdemir; Levent Dalar; Levent Karasulu; Şenay Aydın; Sedat Altın (Pulmonary Medicine)
Obstructive sleep apnea syndrome (OSAS) is a common disorder that can lead to significant cardiovascular complications. Several studies have reported increased platelet activation and aggregation in patients with OSAS. In this study we aimed to show a correlation between mean platelet volume (MPV) and severity of OSAS in patients with OSAS without any overt cardiac disease or diabetes. The polysomnography recordings of 556 consecutive patients admitted to the sleep laboratory between January 2012 and July 2012 were retrospectively evaluated. The relationship between polysomnographic parameters and biochemical parameters was assessed. Polysomnographic results of 200 patients (154 males [77%]; mean age, 44.5 ± 11.4 years) were included. No correlation was observed between MPV and the average oxygen saturation index, the minimum desaturation index, or the oxygen desaturation index in the study population as well as in severe OSAS group (AHI > 30). The only correlation was found between MPV and AHI in the severe OSAS group P=0.010. MPV was not correlated with OSAS severity in patients without any overt cardiac disease or diabetes. These findings raise doubts about the suggestion that MPV might be a marker for OSAS severity, as recommended in earlier studies. Thus, further prospective data are needed.